PENGEMBANGAN KURIKULUM INOVATIF DI SD MUHAMMADIYAH DARUL FALAH UNTUK MENINGKATKAN KARAKTER DAN KOMPETENSI PESERTA DIDIK - Ardianzah, Erwin; Joko Setiono; Sabar Narimo; Bambang Sumardjoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of developing an innovative curriculum at SD Muhammadiyah Darul Falah and the strategies used by teachers in implementing the curriculum. The research employed a qualitative approach with a descriptive design. The research data included curriculum development activities, classroom instructional practices, and the 2025–2026 Curriculum documents. Data sources consisted of the principal, classroom teachers, as well as curriculum documents and instructional materials. Data collection techniques involved observation, in-depth interviews, and documentation studies. Data validity was ensured through source and technique triangulation. Data analysis was conducted using an interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal that innovative curriculum development was carried out through student needs analysis, character-integrated curriculum design, implementation of active project-based learning, and continuous evaluation and reflection. Teacher strategies included character habituation, collaborative learning, role modeling, and individual mentoring, which contributed to the improvement of students’ character and competencies.